Identification of Potential Abnormal Methylation-Modified Genes in Coronary Artery Ectasia - Xiuchun Yang; Yijun Zong; Zhentian Zhang; Yan Zhao; Xueying Gao; Jie Zhang; Qian Hou; Renyi Li; Bing Xiao (International Journal of Genomics)
Background. Coronary artery ectasia (CAE) is an easily recognized abnormality of coronary artery anatomy and morphology. However, its pathogenesis remains unclear. Objectives. This study aimed to identify abnormal methylation-modified genes in patients with CAE, which could provide a research basis for CAE. Methods. Peripheral venous blood samples from patients with CAE were collected for RNA sequencing to identify differentially expressed genes (DEGs), followed by functional enrichment. Then, the DNA methylation profile of CAE was downloaded from GSE87016 (HumanMethylation450 BeadChip data, involving 11 cases and 12 normal controls) to identify differentially methylated genes (DMGs). Finally, after taking interaction genes between DEGs and DMGs, abnormal methylation-modified genes were identified, followed by protein–protein interaction analysis and expression validation using reverse transcriptase polymerase chain reaction. Results. A total of 152 DEGs and 4318 DMGs were obtained from RNA sequencing and the GSE87016 dataset, respectively. After taking interaction genes, 9 down-regulated DEGs due to hypermethylation and 11 up-regulated DEGs due to hypomethylation were identified in CAE. A total of 10 core abnormal methylation-modified genes were identified, including six down-regulated DEGs due to hypermethylation (netrin G1, ADAM metallopeptidase domain 12, immunoglobulin superfamily member 10, sarcoglycan dela, Dickkopf WNT signaling pathway inhibitor 3, and GATA binding protein 6), and four up-regulated DEGs due to hypomethylation (adrenomedullin, ubiquitin specific peptidase 18, lymphocyte antigen 6 family member E, and MX dynamin-like GTPase 1). Some signaling pathways were identified in patients with CAE, including cell adhesion molecule, O-glycan biosynthesis, and the renin–angiotensin system. Conclusions. Abnormal methylation-modified DEGs involved in signaling pathways may be involved in CAE development.